2018
DOI: 10.3892/etm.2018.6343
|View full text |Cite
|
Sign up to set email alerts
|

Laminin‑chitosan‑PLGA conduit co‑transplanted with Schwann and neural stem cells to repair the injured recurrent laryngeal nerve

Abstract: The aim of the present study was to assess the possibility and efficacy of utilizing a laminin-chitosan-poly (lactic-co-glycolic acid), otherwise known as laminin-chitosan-PLGA, nerve conduit with the co-transplantation of Schwann and neural stem cells to repair peripheral nerve defects. Previous in vitro experiments have demonstrated that the three-dimensional structure of the built in fiber filament electrospinning of laminin-chitosan-PLGA nerve conduit is beneficial to the migration and regeneration of nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…Moreover, in vivo experiments revealed that PCL/laminin scaffold supported nerve regeneration (studies on Sprague Dawley rats). Li et al [259] demonstrated that laminin/chitosan/PLGA nerve conduit combined with Schwann cells and neural stem cells promoted nerve regeneration in vivo (studies on Sprague Dawley rats). Interestingly, Salehi et al [219] fabricated biodegradable nerve conduit consisting of PLA, multi-walled carbon nanotubes (MWCNTs), and gelatin nanofibrils (GNFs) combined with the recombinant human erythropoietin-loaded chitosan nanoparticles (rhEpo-CNPs).…”
Section: Nerve Tementioning
confidence: 99%
“…Moreover, in vivo experiments revealed that PCL/laminin scaffold supported nerve regeneration (studies on Sprague Dawley rats). Li et al [259] demonstrated that laminin/chitosan/PLGA nerve conduit combined with Schwann cells and neural stem cells promoted nerve regeneration in vivo (studies on Sprague Dawley rats). Interestingly, Salehi et al [219] fabricated biodegradable nerve conduit consisting of PLA, multi-walled carbon nanotubes (MWCNTs), and gelatin nanofibrils (GNFs) combined with the recombinant human erythropoietin-loaded chitosan nanoparticles (rhEpo-CNPs).…”
Section: Nerve Tementioning
confidence: 99%
“…Scientists have demonstrated that implantation of a poly( l ‐lactic acid) conduit accompanied by neural stem cells and interleukin‐12 in a 3‐mm mouse sciatic nerve gap leads to an increase in the diameter of regenerated nerve fibers and functional nerve recovery (Lee et al, ). It has also been shown that the laminin–chitosan–PLGA nerve conduit combined with cotransplantation of neural stem cells and SCs can contribute to the rat recurrent laryngeal nerve regeneration (Li, Yu, Men, Chen, & Wang, ).…”
Section: Transplantation Of Cell‐seeded Nerve Conduits For Peripheralmentioning
confidence: 99%
“…Various anesthetic drugs with different doses are used for anesthetizing the rats. The drugs and doses that are often used for this purpose include ketamine (60 mg/kg) and xylazine (6 mg/kg; Hansen et al, ), ketamine hydrochloride (1.15 μl/g) and xylazine hydrochloride (0.5 μl/g; Hong et al, ), intraperitoneal injection of 10% choral hydrate (400 mg/kg; Li et al, ), intraperitoneal injection of 10% chloral hydrate (300 ml/100 g bwt; Zhuang et al, ), ketamine hydrochloride (1.15 μl/g) and xylazine hydrochloride (0.5μl/g; Hong et al, ), 45 mg/kg pentobarbital sodium (Wang, Yang, Wu, Zhang, & Wang, ), inhalation of isoflurane/air mixture (5% and 3%; Kriebel et al, ), ketamine (50−100 mg/kg bwt, ip) and xylazine (5 mg/kg bwt, ip; Das et al, ), ketamine (100 mg/kg), and xylazine (10 mg/kg; Delaviz et al, ). In addition, initial anesthesia can be induced by isoflurane 3.5% (for induction) at a flow rate of 800 ml/min, and anesthesia can be maintained by isoflurane 2.5% (for maintenance) during the procedure (Teuschl et al, ).…”
Section: The Necessary Work Before During and After The Conduit Impmentioning
confidence: 99%
See 1 more Smart Citation
“…3 RLNs invaded by tumors require excision; therefore, RLN defects occur in such patients. Although various methods to regenerate defected RLNs have been reported, [4][5][6][7][8][9][10][11] no consistently effective treatments are currently available because they lead to insufficient functional recovery and misdirected innervation. 12 At present, preventing laryngeal muscle atrophy by maintaining nerve continuity is the only feasible treatment method for injured RLNs.…”
Section: Introductionmentioning
confidence: 99%